Study of mythopoetic primitivism in a brief poem by mario de andrade Study of mythopoetic primitivism in a brief poem by mario de andrade - Robert DiAntonio (Ilha do Desterro, 2008)
The weapon of poetry turns against natural
things and wounds or murders them... to
construct something that is not a copy of
"nature" and yet possesses substance of
its own is a feat which presupposes
nothing less than genius.
Jose Ortega y Gassed

The literary ballad, an increasingly popular genre this
century, consciously attempts to emulate the mythic and
primitive aspects of the orally transmitted folk ballad. "A
Serra do Rola-MOca" by Mario de Andrade masterfully exemplifies the consummate depth and brilliance that the modern folk ballad is capable of attaining.
Upon superficial analysis this work appears to be nothing
more than a simple folk narrative, but in essence it emxrcpasses a contemporary mytho-poetic vision of reality rooted in deep psychic and primal elements. This primal vision is subliminally accessable and interpretable only in terms of a psychological analysis of the subject matter. In the work at hand, Andrade creates a personal mythology, one which remains poignantly faithful to the common font of animistic primitivism common to all mythologies. The weapon of poetry turns against natural
things and wounds or murders them... to
construct something that is not a copy of
"nature" and yet possesses substance of
its own is a feat which presupposes
nothing less than genius.
Jose Ortega y Gassed

The literary ballad, an increasingly popular genre this
century, consciously attempts to emulate the mythic and
primitive aspects of the orally transmitted folk ballad. "A
Serra do Rola-MOca" by Mario de Andrade masterfully exemplifies the consummate depth and brilliance that the modern folk ballad is capable of attaining.
Upon superficial analysis this work appears to be nothing
more than a simple folk narrative, but in essence it emxrcpasses a contemporary mytho-poetic vision of reality rooted in deep psychic and primal elements. This primal vision is subliminally accessable and interpretable only in terms of a psychological analysis of the subject matter. In the work at hand, Andrade creates a personal mythology, one which remains poignantly faithful to the common font of animistic primitivism common to all mythologies.